Optimization of Lactic Fermented Beverages: Integrating Trametes Versicolor Mycelium and Pleurotus ostreatus Extract for Enhanced Functional Properties - Nguyen Thi-Bich Hang; Vo Van Minh; Tanaka Munehiro; Bui Duc Thang; Nguyen-Sy Toan; Dang Minh Nhat; Chi Cuong-Doan (Mycobiology)
This investigation involved the addition of Trametes versicolor mycelium to Pleurotus ostreatus extract, which was subsequently fermented using Lactobacillus plantarum to improve the quality of the fermented beverage. The concentration of total dissolved solids (oBrix) generally diminishes with prolonged fermentation time, whereas it increases with the addition of T. versicolor mycelium. The pH values markedly decreased after 12 h, thereafter stabilizing after 24 and 48 h of fermentation, oscillating between 3.04 and 3.32. The total acid content (TAC) escalated in direct correlation with the mycelium ratio and fermentation length, with TAC values spanning from 6.617 to 10.678 g/L at a 1.0% mycelium addition. The ABTS+ antioxidant capacity ascended in direct correlation with the quantity of T. versicolor mycelium incorporated, attaining values of 58.13%, 49.63%, and 48.44% after 12, 24, and 48 h in CT6, respectively. Nonetheless, this ability exhibited a progressive decline over the fermenting period. The addition of T. versicolor mycelium effectively stimulated the proliferation of L. plantarum WCFS1, achieving a high cell density in the treatment supplemented 0.6% T. versicolor mycelium (CT4) after 12, 24, and 48 h of fermentation. The capacity of inhibiting harmful bacteria was maximized with the addition of 1.0% mycelium, resulting in an inhibition zone width of 13.42 mm for Escherichia coli ATCC 85922 after 48 h and 16.65 mm for Staphylococcus aureus ATCC 25023 after 24 h of fermentation. The fermented beverage had the greatest sensory score with the addition of 0.6% mycelium after 24 h of fermentation. The findings revealed significant potential for the manufacture of natural-based functional beverage industry.